Anxiety, depression, and offending in the Columbia County longitudinal study: A prospective analysis from late adolescence to middle adulthood. (May 2019) - Huesmann, L. Rowell; Boxer, Paul; Dubow, Eric F.; Smith, Cathy
Abstract: Purpose: We use data from a community sample, the Columbia County Longitudinal Study, which followed participants from childhood through adulthood, to examine the longitudinal relations between mental health (serious anxiety and serious depression) and offending across three waves of data collection (ages 19, 30, and 48). Method: Participants were from the Columbia County Longitudinal Study (436 males and 420 females). The youth, their parents, and peers were first interviewed when the youth were age 8; the youth were later interviewed at ages 19, 30, and 48. Results: We found significant longitudinal relations from offending to experiencing subsequent severe anxiety and weaker longitudinal relations from experiencing severe anxiety to subsequent offending. For the relation between offending and severe depression, we found similar but somewhat weaker longitudinal associations. Cross-lagged longitudinal structural modeling analyses controlling for the continuity of offending, anxiety, and depression and for family socio-economic status and education were conducted to test the plausibility of alternative causal effects. Conclusions: The analyses suggest that it is more plausible to conclude that offending is stimulating serious anxiety and depression than to conclude that anxiety and depression are stimulating offending. These results mirror what has been found previously about general aggressive behaviour.